2003
DOI: 10.1111/j.1365-313x.2008.03782.x
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin‐ and Dynamin‐Dependent Coated Vesicle Formation from Isolated Plasma Membranes

Abstract: We have developed a new rapid cell-free assay for endocytic clathrin-coated vesicle formation using highly purified rat liver plasma membrane sheets. After incubation in the presence of cytosol and nucleotides, released vesicles were collected by high-speed centrifugation and incorporated cargo receptors were detected by Western blotting. Three different cargo receptors were internalized into vesicles while a receptor, known to be excluded from coated pits, was not. The recruitment of cargo receptors into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 72 publications
3
57
0
Order By: Relevance
“…Alternatively, GTP hydrolysis by assembled dynamin may function to dismantle the fission machinery for recycling in vivo. Indeed, GTP hydrolysis in vitro has been shown to trigger the rapid disassembly of dynamin (21,28), and this interpretation would be consistent with recent observations that GTP hydrolysis by dynamin may not be required for a single round of vesicle formation in vitro (29). There is precedence for this model in that GTP hydrolysis is required for the in vivo function and recycling of other GTPases such as Sar, Arf, SRP54, and SRP receptor, although GTPase defective mutants of each of these proteins are able to support single rounds of activity in vitro (30 -34).…”
Section: Fig 4 Transferrin Internalization In Cells Overexpressing supporting
confidence: 72%
“…Alternatively, GTP hydrolysis by assembled dynamin may function to dismantle the fission machinery for recycling in vivo. Indeed, GTP hydrolysis in vitro has been shown to trigger the rapid disassembly of dynamin (21,28), and this interpretation would be consistent with recent observations that GTP hydrolysis by dynamin may not be required for a single round of vesicle formation in vitro (29). There is precedence for this model in that GTP hydrolysis is required for the in vivo function and recycling of other GTPases such as Sar, Arf, SRP54, and SRP receptor, although GTPase defective mutants of each of these proteins are able to support single rounds of activity in vitro (30 -34).…”
Section: Fig 4 Transferrin Internalization In Cells Overexpressing supporting
confidence: 72%
“…Clathrin provides a scaffold to bind adaptors, and accessory factors involved in cargo recognition, membrane curvature and uncoating (Conner and Schmid, 2003;Kirchhausen, 2000;Traub, 2005). Formation of AP-1 and AP-2 vesicles requires clathrin both in vivo and in vitro (Conner and Schmid, 2003;Hinrichsen et al, 2006;Kirchhausen, 2000;Miwako et al, 2003;Pagano et al, 2004;Traub, 2005). By contrast, in vivo and in vitro data on the role of clathrin in AP-3 vesicle formation are conflicting.…”
Section: The Elusive Role Of Clathrin In Ap-3 Vesiculationmentioning
confidence: 99%
“…In addition, many regulatory genes, including members of the WRKY and NAC transcription factor (TF) families and components of upstream signalling networks, are induced at the onset of senescence (Lim et al , 2007; Balazadeh et al , 2008; Breeze et al , 2011). Furthermore, leaf senescence is controlled by epigenetic mechanisms (Ay et al , 2009; Brusslan et al , 2012; Humbeck, 2013). Recent analyses have shown that senescence can be induced by separate, but interacting regulatory pathways (Guo and Gan, 2012).…”
Section: Introductionmentioning
confidence: 99%